2020
DOI: 10.1038/s41598-020-69165-x
|View full text |Cite
|
Sign up to set email alerts
|

Pollution characteristics and ecological risk assessment of heavy metals in paddy fields of Fujian province, China

Abstract: to analyze the concentration, spatial distribution patterns, and ecological risks of heavy metals (Cd, Cr, Pb, As, Cu, Ni and Co), 272 topsoil samples (0-20 cm) were collected from paddy fields in Fujian province in July 2017. The results revealed that the mean concentration of all heavy metals exceeded the background values in Fujian province, with the mean concentration of Cd being 5.20 times higher than its background. However, these concentrations of heavy metals were lower than their corresponding nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
2
29
3
Order By: Relevance
“…Compared to EF of Co in IA, KS, an NE (0.10, 0.90, 1.03) respectively, it was lower than EF of Co (5.33) demonstrated by Odat, 2015 [44]. As values in the current study showed in Table 3 had lower concentrations compared with the investigated levels in soils in paddy fields of Fujian province in China presented a mean value of 22.60 [28]. However, Co mean values were the same in the current study in IA as reported by [28], but lower than estimated in KS and NE (Table 3).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Compared to EF of Co in IA, KS, an NE (0.10, 0.90, 1.03) respectively, it was lower than EF of Co (5.33) demonstrated by Odat, 2015 [44]. As values in the current study showed in Table 3 had lower concentrations compared with the investigated levels in soils in paddy fields of Fujian province in China presented a mean value of 22.60 [28]. However, Co mean values were the same in the current study in IA as reported by [28], but lower than estimated in KS and NE (Table 3).…”
Section: Discussioncontrasting
confidence: 58%
“…The factor 1.5 is the background matrix correction factor for minimizing the impact of possible variations in the background values (it is used because of the possible variations in background values for a given metal in the environment as well as exceedingly small anthropogenic impacts) that may be attributed to lithologic variations or impacts in the soils [29]. Muller (1969) categorized I geo index into seven class indicators that are used to define the degree of metal contamination according to the criteria and these classifications are shown in Table 1.…”
Section: Geo Accumulation Index (I Geo)mentioning
confidence: 99%
“…The GB values were calculated as means of data compiled from the specialty literature (see Table 1). This index consists of seven classes: uncontaminated (I geo ≤ 0); uncontaminated to moderately contaminated (0 < I geo ≤ 1); moderately contaminated (1 < I geo ≤ 2); moderately to heavily contaminated (2 < I geo ≤ 3); heavily contaminated (3 < I geo ≤ 4); heavily to extremely contaminated (4 < I geo ≤ 5); and extremely contaminated (I geo ≥ 5) [18].…”
Section: Pollution Assessmentmentioning
confidence: 99%
“…Because its effects on animals are cumulative, it is toxic to livestock and humans at lower concentrations than to plants. Compare with other heavy metals, Cd was found to be the main components contributing to the potential health and ecological risks in China by the latest studies 1,2 . The Joint Expert Committee on Food Additives (JECFA) has established a health-based guidance value for Cd (25 µg kg − 1 bodyweight per month) 3 , and the Codex Alimentarius Commission has adopted a maximum concentration of 0.4 mg kg − 1 for Cd in white rice grain 4 .…”
Section: Introductionmentioning
confidence: 99%